Fundamentals of differential equations - Nagle, R. Kent; Saff, Edward B. 1944-; Snider, Arthur David 1940- (Pearson Education Limited, 2019)
Fundamentals of Differential Equations presents the basic theory of differential equations and offers a variety of modern applications in science and engineering. This flexible text allows instructors to adapt to various course emphases (theory, methodology, applications, and numerical methods) and to use commercially available computer software. For the first time, MyLab (TM) Math is available for this text, providing online homework with immediate feedback, the complete eText, and more.